Neurenteric Cysts Found on the Outer Membrane of a Subdural Haematoma. (10th September 2013) - Takahashi, Satoshi; Tanizaki, Yoshio; Akaji, Kazunori; Kano, Tadashige; Mihara, Ban; Masawa, Nobuhide
Abstract : We report on a patient initially diagnosed with a chronic subdural haematoma that was resistant to treatment. After the second burr hole craniostomy within a half month failed to resolve the subdural haematoma (SDH), we performed a craniotomy to identify the point of bleeding. Macroscopic evaluation showed that most of the outer membrane of the SDH was transparent; however, further examination revealed the presence of multiple white regions. Pathologic examination showed that the white regions were fluid filled and surrounded by columnar ciliated epithelial cells. These lesions were pathologically diagnosed as neurenteric cysts. To our knowledge, this is the first report on a patient with neurenteric cysts found on the outer membrane of a CSDH. We agree that a craniotomy is a treatment of last resort for recurrent CSDHs; however, sometimes this procedure can be very useful for identifying underlying causes of obstinate SDHs as well as for their treatment.